2014
DOI: 10.1177/0272989x14543107
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and Explaining Differences in the Magnitude, Content, and Sensitivity of Utilities Predicted by the EQ-5D, SF-6D, HUI 3, 15D, QWB, and AQoL-8D Multiattribute Utility Instruments

Abstract: Results indicate that instruments measure related but different constructs. They imply that commonly used instruments systematically discriminate against some classes of services, most notably mental health services. Differences in the instrument scales imply the need for transformations between the instruments to increase the comparability of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 22 publications
(30 reference statements)
7
103
1
Order By: Relevance
“…There are four different versions of the ASCOT instrument [59], to be used in different circumstances, and three different ICECAP measures for different patient types (see above), plus the O-CAP variations and instruments developed specifically to assess quality of life in Malawi and chronic pain. Not unlike the multiple MAUIs [37], there is no gold standard; while they all purport to measure capability they will be measuring different aspects of it. NICE technology appraisals avoid this given the stated preference for the use of the EQ-5D, at least in terms of adult conditions; there is less specificity around measuring HR-QoL for children, and the public health and social care guidance are even less prescriptive.…”
Section: Outstanding Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four different versions of the ASCOT instrument [59], to be used in different circumstances, and three different ICECAP measures for different patient types (see above), plus the O-CAP variations and instruments developed specifically to assess quality of life in Malawi and chronic pain. Not unlike the multiple MAUIs [37], there is no gold standard; while they all purport to measure capability they will be measuring different aspects of it. NICE technology appraisals avoid this given the stated preference for the use of the EQ-5D, at least in terms of adult conditions; there is less specificity around measuring HR-QoL for children, and the public health and social care guidance are even less prescriptive.…”
Section: Outstanding Issuesmentioning
confidence: 99%
“…Note that one of the most detailed comparison studies, the multiinstrument comparison (MIC) study includes ICECAP-A and six other MAUIs (EQ-5D-5L, AQoL-8D, HUI3, 15D, QWB and the SF-6D)[37].…”
mentioning
confidence: 99%
“…18 Broadly speaking, direct methods are considered theoretically superior but more administratively burdensome to implement than indirect methods; indirect methods are more convenient and can easily be integrated into clinical trials, but have practical limitations in their sensitivity to effects. 19,20 Both methods produce theoretically equivalent results, although in practice differences across methods have been observed. 21 …”
Section: Methodsmentioning
confidence: 99%
“…A further cited limitation is the discrepancies in utility values when measured with different preference-based instruments [20][21][22][23][24]. Richardson et al [25] compared the utilities in patients from seven disease areas and compared them with values from healthy members from the public using six instruments, including the EQ-5D, SF-6D, HUI3, 15D, Quality of Well-Being, and Assessment of Quality of Life (AQoL). The results revealed that the magnitude of utility difference varied with the choice of instrument by more than 50% for every disease group.…”
Section: Introductionmentioning
confidence: 99%